Non-setting, injectable biomaterials containing particulate hydroxyapatite can increase primary stability of bone screws in cancellous bone. (November 2018) - Solana Muñoz, Jorge; Kettenberger, Ulrike; Procter, Philip; Pioletti, Dominique P.
Abstract: Background: Fracture fixation in weak bone is still a clinical challenge. Screw augmentation was shown to successfully increase their primary stability. The currently used calcium phosphate or polymeric bone cements, however, present important drawbacks such as induced toxicity and/or impaired bone neo-formation. A new approach to enhance bone screw primary stability without affecting bone formation is the use of non-setting, calcium phosphate loaded soft materials as the augmentation material. Methods: Two types of biomaterials (non-crosslinked hyaluronic acid as viscous fluid and agar as hydrogel) were loaded with 40 wt/vol% of hydroxyapatite particles and characterized. The screw augmentation effect of all materials was evaluated through pull-out tests in bovine cancellous bone and compared to the non-augmented situation (control). The bone mineral density of each test sample was measured with μCT scans and was used to normalize the pull-out strength. Findings: Both materials loaded with hydroxyapatite increased the normalized pull-out strength of the screws compared to control samples and particle-free materials. This counter-intuitive augmentation effect increased with decreasing bone mineral density and was independent from the type of the soft materials used. Interpretation: We were able to demonstrate that non-setting, injectable biomaterials loaded with ceramic particles can significantly enhance the primary stability of bone screws. This material combination opens the unique possibility to achieve a screw augmentation effect without impairing or even potentially favoring the bone formation in proximity to the screw. This effect would be particularly advantageous for the treatment of osteoporotic bone fractures requiring a stabilization with bone screws. Highlights: Soft materials with 40 wt/vol% hydroxyapatite particles increase bone screw stability. Augmentation effect not dependent on material type but on presence of hydroxyapatite Tested materials are injectable through a cannula with a diameter smaller than 1 mm. Injectable materials with hydroxyapatite can be a new strategy for screw augmentation.